Application of rapid prototyping in medical engineering - Wan Yusoff, Wan Ahmad Yusmawiza; Mohamad Ali, Hasanudin Hafis; Md. Shukri, Md. Amir Hamzah (2011)
The purpose of this project is to implement the use of rapid prototyping technology as a great value tool in supporting medical activity. It is possible to produce three-dimensional model from two-dimensional images from Computerized Tomography (CT) scan where the machine provides images data are used to capture. Rapid Prototyping (RP) is a technology from mechanical engineering that is used to fabricate physical prototypes called biomedical model that can be used for surgical planning. The models produced by using RP bring the significant in educational and pre-medical surgical environments. It can simplify the complex surgical procedures and the visualization of anatomical structures in educational environment. A biomedical model analysis after the fabrication process is introduced to makes the result more trustful. Thus, it was demonstrate that biomedical model can help surgical plan and at the same time they can contribute to reduce costs, surgical times and infection risks in health care system.